Factors influencing farmers{u2019} decision to grow and consumers{u2019} decision to purchase exotic vegetables : a case study of Pune, in Maharashtra, India - Raut, Nisha Natha; Datta, Avishek; Kuwornu, John K. M.; Loc, Thai Nguyen; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Demand-driven exotic vegetables production is suitable for farmers to adopt the new farming pattern as they have assured market through contract with the consumers. Exotic vegetable market is growing at the rate of 15 to 20% per annum. The people in India are now developing new test buds to accept new food items. Preparation of these food items need many exotic vegetables like Lettuaca sativa, Asparagus officinalis, Zea mays, Brassica oleraceae, Solanum esculentum, Petroselinum crispum, Allinum porrum etc. The overall objective of the study the factors which influence farmers and consumers towards exotic vegetables. The study aims to assess perceptions of farmers{u2019} and consumers regarding exotic vegetables. And determine the factors influencing farmers{u2019} decision to grow and consumers{u2019} decision to purchase exotic vegetables. The study is focused on the Pune district of Maharashtra, India. Total number of respondents were 200 consumers and 163 farmers. For analysis Weighted Average Index (WAI) - use to assess the farmers and consumers perception towards exotic vegetables. Logit Regression Model - use to determine the factors influence farmers to grow and consumers decision to purchase exotic vegetables. The results showed that the major education level of farmers was primary school, secondary school and graduates. 52% of the total respondents reasoned that the trend of exotic vegetables had increased. Exotic vegetable growers were satisfied with the government support, fair price for produce, fixed income, assured market, high production, and high production in less investment. The logit model was fitted which shows that education, Farm investment, Government support, other financial support, and exchange knowledge with other farmers in different area were the factors influence farmers to grow exotic vegetables. Majority of consumers were students and business owners. Most of the consumers was graduates and post-graduates. The mass media plays a vital role to create awareness about exotic vegetables among the consumers. The attitude, Familiarity and differential cognition, has an encouraging effect on purchase intension and willingness to pay premium price for exotic vegetables. The consumer purchase high value product because to try something new and different from others. The logit model was fitted which shows that education, Source of awareness and ready to spend extra money on quality product were the factors influence consumers to purchase exotic vegetables. The study provides a better understanding of farmers and consumers attitude, and perceptions towards exotic vegetables. The study also provides guidelines and suggestions for retailers and markets who are dealing with the exotic vegetables and aim to expanding the exotic vegetables market.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management in Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2019
Keywords: Cooking (Vegetables) -- India; Tropical vegetables -- India; Consumers -- India -- Attitudes